2013
DOI: 10.1016/j.foodchem.2012.08.028
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for the promotion of quercetin glycoside absorption by megalo α-1,6-glucosaccharide in the rat small intestine

Abstract: The presence of an α-1,6-glucosaccharide enhances absorption of water-soluble quercetin glycosides, a mixture of quercetin-3-O-β-d-glucoside (Q3G, 31.8%), mono (23.3%), di (20.3%) and more d-glucose adducts with α-1,4-linkage to a d-glucose moiety of Q3G, in a ligated small intestinal loop of anesthetized rats. We prepared α-1,6-glucosaccharides with different degrees of polymerization (DP) enzymatically and separated them into a megalo-isomaltosaccharide-containing fraction (M-IM, average DP=11.0) and an olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…In the former studies, it has shown that the bioavailability of quercetin glycoside was promoted by the ingestion of a-1,6-glucosaccharides, this was because the supplementation of a-1,6-glucosaccharides could enhance the content of Q in the water-phase fraction (Shinoki et al, 2013). Another previous study indicated that it could influence on the plasma kinetics of hypericin in the presence of procyanidin B2 and hyperoside, which contains six phenolic hydroxyls at its molecular skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In the former studies, it has shown that the bioavailability of quercetin glycoside was promoted by the ingestion of a-1,6-glucosaccharides, this was because the supplementation of a-1,6-glucosaccharides could enhance the content of Q in the water-phase fraction (Shinoki et al, 2013). Another previous study indicated that it could influence on the plasma kinetics of hypericin in the presence of procyanidin B2 and hyperoside, which contains six phenolic hydroxyls at its molecular skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…B). FOS has shown to increase absorption and bioavailability of Q3G , which might be involved in the enhancement of Q3G‐induced GLP‐1 secretion. The detailed mechanism needs to be further examined.…”
mentioning
confidence: 99%
“…Interestingly, previous research has suggested that non-digestible oligosaccharides can enhance intestinal absorption of polyphenols, which is possibly due to the fact that non-digestible oligosaccharides increase water-solubility of flavonoids and inhibit their degradation in gut (10, 28). It is also widely recognized that TC can undergo Phase II biotransformation mainly including UGT and SULT in intestinal epithelial cells, which may greatly contribute to their first-pass metabolism (14, 27, 29).…”
Section: Discussionmentioning
confidence: 99%